2014
DOI: 10.1063/1.4882879
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of InN/GaN short period superlattices to mimic disordered alloys

Abstract: Articles you may be interested inNet electron-phonon scattering rates in InN/GaN multiple quantum wells: The effects of an energy dependent acoustic deformation potential Appl. Phys. Lett. 105, 063115 (2014); 10.1063/1.4893158 Band gaps and internal electric fields in semipolar short period InN/GaN superlattices Appl. Phys. Lett.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Considerable efforts have already been made for understanding the electronic band structure of III–V nitride alloys (InGaN, AlGaN, and AlInN) and SLs (InN/GaN and GaN/AlN) . However, there are few reports in the open literature on the bandgap and on the synthesis of InN/AlN SLs.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable efforts have already been made for understanding the electronic band structure of III–V nitride alloys (InGaN, AlGaN, and AlInN) and SLs (InN/GaN and GaN/AlN) . However, there are few reports in the open literature on the bandgap and on the synthesis of InN/AlN SLs.…”
Section: Introductionmentioning
confidence: 99%
“…Ultra-thin In x Ga 1−x N/GaN quantum wells have concentrated significant interest for use in band-gap engineering [1][2][3][4][5]. Such quantum wells can, in principle, accommodate a high indium content while remaining pseudomorphic.…”
Section: Introductionmentioning
confidence: 99%
“…The ultra-thin QWs can sustain large elastic strains without plastic relaxation, and reduce the QCSE. Theoretical investigations have shown that the strain and bandgap of In x Ga 1− x N/GaN SLs can be adjusted through the QW and barrier thicknesses 7 11 . In addition to providing bandgap tunability, MQW SLs allow for strain transfer to the barriers, and may reduce the compositional fluctuations and indium clustering that significantly affect the bandgap 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%